Panel Estimates of Union Effects on Wages and Wage Growth - Polachek, Solomon W.; Wunnava, Phanindra V.; Hutchins, Michael T. (The Review of Economics and Statistics, 1987)
Solomon W. Polachek, Phanindra V. Wunnava, Michael T. Hutchins, Panel Estimates of Union Effects on Wages and Wage Growth, The Review of Economics and Statistics, Vol. 69, No. 3 (Aug., 1987), pp. 527-531